Intercultural Communicative Competence in Teaching Sociocultural Contents of Spanish as a Foreign Language: Analysis of History Teachers' Lesson Plans - Pozzo, María Isabel Rita (2014)
This paper proposes the application of the concept of intercultural communicative competence in Spanish speaking teachers teaching sociocultural contents of Spanish as a foreign language (SFL). Specifically, subjects under investigation are Argentine history teachers in charge of a course concerning the history of their country aimed at young foreigners of different nationalities. We organized the course as an intercultural device in a quasi-experimental design comprising prefacto (a personal language biography and intercultural experiences survey), the de facto (planning, selection and / or creation of educational materials for the class and its implementation) and the post-facto (individual written self-assessment of their own performance). The classes taught by rotating teachers provide abundant empirical data for the analysis of this competence in the pre-active, active and post active stages (Jackson, 1991). The situation is particularly interesting as it is about native teachers who teach about their own culture in their native language to students of different socio-linguistic backgrounds interested in the proposal. As part of this major investigation, this paper is devoted to analyzing the lesson plans written by teachers for their classes. From its components (objectives, contents and activities), we searched the main indicators of intercultural communicative competence according to its main theoretical models and the integrated approach of cultures and languages (enfoque integrado de culturas y lenguas (EICLE- in Spanish or Content and Language Integrated Learning-CLIL-). The conclusions point out which aspects have to be promoted in teacher training for the proper development of this competence.